Non-traditional Micromachining Processes Fundamentals and Applications - Kibria, Golam; Bhattacharyya, B.; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents a complete coverage of micromachining processes from their basic material removal phenomena to past and recent research carried by a number of researchers worldwide. Chapters on effective utilization of material resources, improved efficiency, reliability, durability, and cost effectiveness of the products are presented. This book provides the reader with new and recent developments in the field of micromachining and microfabrication of engineering materials.
Non-traditional micromachining processes: opportunities and challeges -- Electrical discharge micro-hole drilling process employing additive mixed dielectrics -- Tool wear compensation in micro EDM -- Advances on ultrasonic micro machining (USMM) process -- Electrochemical discharge micro-machining of engineering materials -- Electrochemical micromachining (EMM) -- Electrochemical micromachining of titanium and its alloys -- Laser micro-turning process of aluminium oxide ceramic using pulsed Nd:YAG laser -- Fiber Laser Micro-Machining of Engineering Materials -- Laser beam micro cutting -- Underwater laser microchanneling.
Keywords: Ceramic materials; Materials; Manufactures; Ceramics; Materials Engineering; Machines, Tools, Processes